Genealogia świętego Jana Pawła II - GRYGIEL, Ludmiła (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2014)
The article attempts a description of how Karol Wojtyła implemented in his life, from childhood to old age, the universal call to holiness. The author fo-cuses on the persons who became assistance and paragons to St. John Paul II. She discusses not only personalities he actually met, like for instance Bp. Jan Pietraszko, Jerzy Ciesielski or Hanna Malewska, but also saints who lived in remote epochs, like St. Stanislaus of Szczepanów, St. Hedwig, Queen of Po-land, and Br. Albert Chmielowski. Following into the footprints of others, John Paul II found his own, unique form of the perfect Christian life. The practice of his life involved contemplation and anthropological insight into holiness, which he perceived as a ‘challenge to the Christian life’ and a refl ection of the dignity of the human person.